LEBANO (Lemari Pengering Pakaian Berbasis Arduino Uno) Sebagai Solusi Alternatif Pengering Pakaian - Deny Nusyirwan (Jurnal Teknologi dan Terapan Bisnis, 2019)
Indonesia is a country that has a tropical climate where there are only two seasons namely summer and rainy season. During the summer, the biggest source of energy used to dry clothes is sunlight. Whereas during the rainy season there are a lot of problems that arise or obstacles experienced by some people to dry clothes, especially for school children ... Often when on the way to the workplace or place where the school is caught in the rain so the clothes used are a little moist or even wet. From these problems, a prototype was designed, namely a clothes dryer using wind produced through a fan. This prototype is called LEBANO (Arduino Uno based clothes dryer cabinet). Lebano uses Arduino Uno as a microcontroller and Dht11 temperature sensor as a detector for the humidity temperature of an object. When the object's humidity is still below a certain limit, the fan will still rotate. The process of this research begins with a social approach by carrying out activities with prospective users of innovation, which is integrated with the approach to design thinking to be able to produce technology-based innovations that are beneficial to these prospective users. From the results of testing with prospective users, satisfactory results were obtained in terms of ease of use of technology, benefits of innovation and function in prototypes.